Forming Tourism Higher School Students’ Readiness for Foreign Language Communication in Ukraine Tertiary level - Babushko, Svitlana Rostyslavivna; Halytska, Maiia; Solovei, Myroslav (International Journal of Language Education, 2020)
AbstractThe article reveals the dynamics of forming readiness for foreign language communication of future tourism employees in higher school. To trace it, a complex of theoretical and empirical methods was used: literature overview, comparison, systematization and generalization, questioning, testing, pedagogical observation, survey, statistical calculations of the obtained results. In the pedagogical experiment the accent was put on the content component of the formation of students’ readiness for foreign language communication. 600 university students participated in it. Firstly, introductory level of students’ knowledge was defined. Secondly, the dynamics of forming students’ readiness for foreign language communication was checked in four types of activities: listening, reading, writing and speaking.   The authors worked out the original pedagogical technology which included practical classes, independent work, special courses, excursions, gamification, system of exercises and tasks based exclusively on tourism industry oriented content. The analysis of the molding experiment results illustrated that the level of students’ readiness for foreign language communication according to the content criterion significantly increased.